Realization of competency approach at a higher school: technological aspect - Luzan, Petro (Professional Pedagogics, 2012)
In the article basic approaches to planning the organizational forms concerning problem-developing training are highlighted. Potentials of informative lecture, problem lecture, educational planning in relation to realization of ideas of competency methodology are considered.
Keywords: competency; methodology; training methods; education results